Lean Enterprise - Humble, Jez; Molesky, Joanne; O'Reilly, Barry (O'Reilly Media, Incorporated, 2019)
How well does your organization respond to changing market conditions, customer needs, and emerging technologies when building software-based products? This practical guide presents Lean and Agile principles and patterns to help you move fast at scale-and demonstrates why and how to apply these methodologies throughout your organization, rather than with just one department or team. Through case studies, you'll learn how successful enterprises have rethought everything from governance and financial management to systems architecture and organizational culture in the pursuit of radically improved performance. Adopting Lean will take time and commitment, but it's vital for harnessing the cultural and technical forces that are accelerating the rate of innovation. Discover how Lean focuses on people and teamwork at every level, in contrast to traditional management practices Approach problem-solving experimentally, by exploring solutions, testing assumptions, and getting feedback from real users Lead and manage large-scale programs in a way that empowers employees, increases the speed and quality of delivery, and lowers costs Learn how to implement ideas from the DevOps and Lean Startup movements even in complex, regulated environments.